2020
DOI: 10.1007/s11423-020-09851-9
|View full text |Cite
|
Sign up to set email alerts
|

An international perspective for ‘Improving teacher professional development for online and blended learning: a systematic meta-aggregative review’

Abstract: This paper is in response, from an international perspective, to the manuscript entitled “Improving teacher professional development for online and blended learning: a systematic meta-aggregative review” (Philipsen, B., Tondeur, J., Pareja Roblin, N. et al . 2019). The impact of the manuscript has been reinforced by the claims of international organisations like UNESCO and ILO, as far as they highlight that Teacher Professional Development (TPD) for Online and Blended Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 1 publication
0
16
0
1
Order By: Relevance
“…Several studies [54,55] have addressed this demand for future teachers at Faculties of Education, as well as for active teachers by means of Professional Development programs. It can be said that COVID-19 has emphasized the importance of teacher professional development for online and blended learning [56].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [54,55] have addressed this demand for future teachers at Faculties of Education, as well as for active teachers by means of Professional Development programs. It can be said that COVID-19 has emphasized the importance of teacher professional development for online and blended learning [56].…”
Section: Discussionmentioning
confidence: 99%
“…After this pandemic, teachers will play new roles. Therefore, the future of learning requires carefully generating the new roles teachers must play in online and blended learning (OBL) and an international perspective in both TPD and faculties of education will help to build resilient education systems for the long term (Portillo & de la Serna, 2020).…”
Section: "I Attended Webinars and Online Training Of Kindergarten And Special Education Teachers On The Essential Skills And Strategies Tmentioning
confidence: 99%
“…A study of eleven academics over six years from Finland revealed that TPD that sought to build reflective practice and peer interaction assisted most in the development of a teacher identity (Nevgi & Lofstrom 2015). Although developed pre-pandemic, responses to the six component TPD framework suggested by Philipsen et al (2019), agree that whilst it provides a useful mechanism to structure a post-COVID TPD discussion (Heap, Thompson & Fein 2020;Lockee 2020;Portillo & Lopez de la Serna 2020) the fact that it was conducted in a West-European context 'is an overall limitation from an international perspective' (Portillo & Lopez de la Serna 2020: 2).…”
Section: Literature Reviewmentioning
confidence: 99%